Fuzzy Logic Untuk Menentukan Lokasi Kios Terbaik Di Kepri Mall Dengan Menggunakan Metode Sugeno - Putri, Anggia Dasa (STKIP PGRI Sumatera Barat, 2016)
Riau Islands Mall under the management of PT Citra Buana Initiative is one of the shopping centers in Batam. Riau Islands Mall covers a total area of 65,000 square meters of retail space, and consists of 4 floors, Riau Islands Mall also provides a shop around the area and a kiosk inside the free rent. Currently Kepri Mall also offers / kiosk that can be used for business products and services. However, Riau Islands Mall are still having difficulties in determining the location of the kiosk best for tenants due to the determination / selection kiosk location still rely on manual way so that they are less accurate, because the stall tenant who often move the location of the kiosk business premises due to feel the position of the location of the kiosk is not suitable / suited to the type of business. The problems that arise in this world sometimes often has no definite answer, fuzzy logic is one method to analyze the system is uncertain. This thesis discusses the application of fuzzy logic on solving the problem of determining the best location in kepri mall kiosk using Sugeno method. The problem is solved by determining the best kiosk location by using three variables as input data, ie: price = 180, position = 7.5, and the size = 14. And the results output from the manual count of 0.85 results in defuzzification obtain and use apps matlab obtained results of 0.86, the results do show the location of the best stall Exactly.Keyword : Determining the best kiosk location , Fuzzy Logic, Fuzzy Sugeno